Erosion stability of sod-podzolic soils in different agricultural fields - Tsyribko, Viktor; Tsybulka, Mikalai; Yukhnovets, Aksana; Zhukova, Inna; Logachev, Ilya (Journal of the Belarusian State University. Ecology, 2025)
Soddy-podzolic soils immediately after mechanical treatment are characterized by very low erosion resistance. The erosive velocity of the water flow does (V∆p) not exceed 11.1 cm/s. Soil resistance to erosion decreases with increasing degree of erosion degradation. The use of eroded soils in soil-protective grass-grain crop rotations helps improve their resistance to erosion. Moderately and highly eroded soils on loess-like loams in grain crop rotation were characterized by low V∆p – 16.5–18.5 cm/s, and in grass-grain crop rotation with alfalfa cultivation – high and medium V∆p – 33.1 and 29 cm/s. With the organomineral fertilizer system, an increase in the anti-erosion resistance of soils was observed compared to the mineral fertilizer system. The eroding velocity of water flow averaged 25.7 cm/s on non-eroded soil, 21.8 cm/s on moderately eroded soil, and 18.5 cm·s-1 on highly eroded soil. The application of lime ameliorants against the background of an organomineral fertilizer system did not lead to an increase in V∆p. A close correlation has been established (r = 0.76) between the erosive velocity of water flow and the weighted average diameter of water-resistant aggregates in the soil.